Detoxification mechanisms of black soldier fly larvae against microcystin-LR - Wenna Bao; Xinying Li; Haifeng Pan; Yingzi Gao; Linan Zhao; Jingsong Liu; Siyi Wang; Yinyi Zhang (Functional & Integrative Genomics, 2026)

Spatiotemporal variations and factors associated with surface urban heat islands in South Asia - Linan Sun; Longjue He; Haojie Liu; Peng Kang; Lan Wang; Jvjie Jia; Yuanzheng Li (Urban Climate, 2026)

Effect of microplastics on arsenic transport in shallow groundwater of coastal transition zones - Yizi Hua; Yuan Xue; Zhi Li; Yuting Zhang; Qinglong Liu; Linan Liu; Jingchun Tang (Water Research, 2026)

Perfluorooctanoic acid (PFOA) disrupts marine carbon sequestration potential of diatom Phaeodactylum tricornutum by regulating carbon-silicon coupling - Zhi Li; Yizi Hua; Yuan Xue; Linan Liu; Yuting Zhang; Lan Wang; Gang Wang; Qiang Li; Jingchun Tang (Journal of Hazardous Materials, 2026)

Cytological and molecular genetic evidence of feminized male gametophyte in the brown alga Saccharina japonica - Xiufeng Zhou; Cailing Yi; Nianchao Xue; Yan Li; Juan Sun; Shuxiu Chen; Yuting Zhai; Liang Shi; Yanling Liu; Nan Zhao; Xia Li; Xiaojie Li; et al. (Algal Research, 2026)

Construction of icariin-loaded bone powder/PLA composite scaffold and its effect on osteogenic differentiation of hADSCs - Weiting Guo; Xinyue Liu; Yingchao Liu; Jingjing Zhu; Langyu He; Yiran Tang; Yuen Yee Cheng; Xiangqin Li; Linan Li; Hongfei Wang; Kedong Song (Tissue and Cell, 2026)

ABEEM/MM Magnesium Force Field for Proteins and Aqueous Solutions - Jing Zhang; Linan Lu; Runqiang Yu; Linlin Liu; Lei Wang; Cui Liu; Lidong Gong; Zhongzhi Yang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Genomic insights into adaptation and microevolution of two novel non-AOA Nitrososphaeria, Acidarchaeum fankouense and Thermosulfuris yongpingense, in acid mine drainage ecosystems - Licao Chang; Xikai Su; Wenzhe Hu; Yun Fang; Jun Liu; Jintian Li; Linan Huang; Wensheng Shu (Systematic and Applied Microbiology, 2026)

A single PCR-based sex marker, Sj-SexI, from conserved SDR gametologue genes: Enhancing efficiency and cross-species applicability in kelp - Liping Liu; Zihan Gai; Yan Li; Yanling Liu; Shuxiu Chen; Xiaojie Li; Weiwei Wang; Linan Zhang (Aquaculture, 2026)

Experimental aerodynamic investigation of a suction sail model - Xinru Du; Jingpu Chen; Linan Guo; Yanxia Wang; Shiliang Hu; Hanfeng Wang; Xiyang Liu (Ocean Engineering, 2026)

Integrated assessment of hydrothermal and diffuse CO2 emissions in the Sangri-Cona rift, southern Tibetan Plateau - Yi Liu; Maoliang Zhang; Wei Liu; Xian-Gang Xie; Linan Wang; Sheng Xu (International Journal of Earth Sciences, 2026)

Heavy metal migration in sediment of ionic rare earth mining basin in China: Microbial-mediated processes and self-adaptation mechanisms - Linan Zhang; Zuwen Liu; Yichun Zhu; Shuai Tian; Jinfeng Zeng; Jiawei Zuo; Zilong Zheng (Journal of Hazardous Materials, 2026)

Humic acid modulates Fe(II) mediated chromium reduction in simulated marine-terrestrial interlaced zones: A double-edged sword effect - Yuan Xue; Yizi Hua; Zhi Li; Yuting Zhang; Linan Liu; Jingchun Tang (Journal of Hazardous Materials, 2026)

Investigation of hydrate formation and flow characteristics within multiphase transmission pipelines employing a constant pressure visualization loop system - Xi Wang; Kaibang Liu; Shouyi Ma; Linan Guan; Zherui Chen; Yan Qin; Jingyue Sun; Cong Chen (Gas Science and Engineering, 2025)

Air layer-engineered Cf@void@SiCnf composites for enhanced electromagnetic wave absorption - Wenzhao Geng; Limeng Song; Yilin Liu; Haoyuan Lei; Peng Liang; Linan Wang; Hailong Wang; Yanqiu Zhu; Mi Tian; Rui Zhang; Zhiyu Min; Bingbing Fan (Chemical Engineering Journal, 2025)

Study on hydraulic condition optimization of a new permeable modular constructed wetland - Fangxing Zhao; Xinwen Zhang; Jianchao Yang; Zhiheng Ye; Shuo Liu; Linan Zhou; Yixin Wang; Zhenghe Xu (Journal of Environmental Chemical Engineering, 2025)

Molecular dynamics insights into polypropylene microplastics adsorption onto PDMS coated sponge - Guifang Liu; Junyi Zhao; Yuxi Zhao; Hairong Mi; Linan Zhu; Chunli Wang; Di Guan (Environmental Pollution, 2025)

Low intensity ultrasound enhances volatile fatty acid production of waste activated sludge: Insights into extracellular polymeric substances and sludge rheological properties - Linan Zhang; Shuai Tian; Shi Yang; Yichun Zhu; Zuwen Liu (Journal of Environmental Management, 2025)

Viral insights into the acidification of sulfidic mine tailings - Xikai Su; Jun Liu; Licao Chang; Wenzhe Hu; Yun Fang; Jintian Li; Linan Huang; Wensheng Shu; Hailiang Dong (Journal of Hazardous Materials, 2025)

Iron-silicon modified biochar for remediation of cadmium/arsenic co-contaminated paddy fields: Is it possible to kill two birds with one stone? - Han Wu; Linan Liu; Jingmin Sun; Xin He; Zichuan Li; Jingchun Tang (Journal of Hazardous Materials, 2025)

Naturally Occurring Epialleles and Their Roles in Response to Climate Change in Birch - Bowei Chen; Tianxu Zhang; Yile Guo; Lesheng Cao; Xu Zhang; Shahid Ali; Renyi Ma; Linan Xie; Jiang Wang; Gaurav Zinta; Shanwen Sun; Guifeng Liu; et al. (Molecular Ecology, 2025)
Epigenetics has been proposed to be an important mechanism that enables plant species to respond and adapt to environmental and climatic fluctuations and is sometimes entirely uncoupled from genetic variation. Nevertheless, the extent of this uncoupling and the contribution of epigenetics to plant responses to global climate change have not been well studied, particularly in forest trees. Here, we generated a high‐quality genome assembly for Betula platyphylla , a key pioneer species in temperate and boreal forest ecosystems, one of the most sensitive areas to global warming. Extensive multi‐omics sequencing of naturally white birch across the 48 provenances captured their full scope of temperate/boreal forests in Northeast China. Using a genome‐wide association study (GWAS), it was shown that over 55% of differentially methylated regions (DMRs) were spontaneous, independent of genetic factors. More than 30% of the spontaneous DMRs were significantly associated with gene expression, that is, potential epialleles, which are primarily involved in metabolism and responses to abiotic stresses; and 1819 of these epialleles were significantly associated with bio‐climatic variables (i.e., climatic epialleles, cEpialleles). Integrating these cEpialleles into a gradient modelling framework revealed that the natural populations of Asian white birch at high altitude/latitude might be most vulnerable to future climates. Our findings highlight the importance of integrating epigenomic and climatic data sets to forecast the adaptive capacity of a key forest species to rapid climate change.

Systematical accumulating and regulating evaluations of leaf functional metabolites in geographically isolated edible medicinal plants of Piper sarmentosum - Liu Ziting; Wu Xiaoqing; Wang Kemei; Bai Yachao; Guo Aimin; Linan Huang; Liao Bin; Zhang Jun (Journal of Plant Physiology, 2025)

Polyploid breeding of Saccharina japonica: Harnessing aposporous reproduction - Pingping Tian; Yan Li; Nianchao Xue; Weiwei Wang; Shuxiu Chen; Yanling Liu; Juan Sun; Guangjin Liang; Juping Zhao; Liang Shi; Nan Zhao; Xia Li; et al. (Aquaculture, 2025)

Potential bacterial resources for bioremediation of organochlorine pesticides and flame retardants recognized from forest soil across China - Jiayu Liu; Jialiang Kuang; Xiangwen Chen; Linan Huang; Zhenqing Shi (Journal of Hazardous Materials, 2025)

Integrated response surface and machine learning approach: Experimental optimization and DFT analysis for NaN3 removal via NaClO oxidation - Yunfeng Tan; Jiangzhou Qin; Shengquan Chang; Shengqiang Ma; Linan Su; Nengsheng Liu; Quanlin Zhao; Xintao Wang; Chenxi Li; Jinmao Ma; Kun Wu; Zhengfang Ye (Journal of Water Process Engineering, 2025)

Designing MXene hydrogels for flexible and high-efficiency electromagnetic wave absorption using digital light processing 3D printing - Yilin Liu; Wenzhao Geng; Linan Wang; Hailong Wang; Rui Zhang; Di Lan; Bingbing Fan (Chemical Engineering Journal, 2025)

Deep CO2 emissions facilitated by localized shear deformation: A case study of the Karakoram fault system, western Tibet - Xian-Gang Xie; Maoliang Zhang; Wei Liu; Yi Liu; Linan Wang; Yunchao Lang; Sheng Xu (Journal of Asian Earth Sciences, 2025)

Remediation of chromium contaminated water and soil by nitrogen and iron doped biochars - Shakeel Ahmad; Xiaomei Liu; Linan Liu; Muhammad Waqas; Junhui Zhang; Muhammad Azher Hassan; Shicheng Zhang; Bo Pan; Jingchun Tang (Science of The Total Environment, 2024)

Phototransformation and photoreactivity of MPs-DOM in aqueous environment: Key role of MPs structure decoded by optical and molecular signatures - Saisai Guo; Linan Liu; Lan Wang; Jingchun Tang (Journal of Hazardous Materials, 2024)

Silver and g-C3N4 co-modified biochar (Ag-CN@BC) for enhancing photocatalytic/PDS degradation of BPA: Role of carrier and photoelectric mechanism - Yaxuan Liu; Chen Yu; Huixia Lu; linan Liu; Jingchun Tang (Environmental Research, 2024)

The divergence of DHN-derived melanin pathways in Metarhizium robertsii - Linan Xie; Yang Liu; Yujie Zhang; Kang Chen; Qun Yue; Chen Wang; Baoqing Dun; Yuquan Xu; Liwen Zhang (World Journal of Microbiology and Biotechnology, 2024)

Enhanced reductive degradation of trichloroethylene by ball milled nitridation of bimetallic Ni-ZVI: Combination effect of electron transfer and catalytic hydrogenation - Yinghao Shi; Dong Wang; Jiaming Guo; Feilong Gao; Linan Liu; Jingchun Tang (Journal of Cleaner Production, 2024)

Heparin mimicking sulfonated polyester synergistically promotes bacterial Infected-Wound healing with ROS responsive cinnamaldehyde based prodrugs - Haiwei Liu; Pengfei Shan; Yingwen Lu; Xiaoyue Lian; Feng He; Jinxiang Xiao; Linan Qiu; Zhenghao Liu; Zuobin Gan; Qingshan Yan; Yupeng Qiu; Wenwen Lin; et al. (Chemical Engineering Journal, 2024)

Iron and silicon modified biochar for enhancing cadmium removal from water: Unveiling the crucial role of iron-induced silicon dissolution - Han Wu; Linan Liu; Yuguo Zhuo; Robert Mark Ellam; Keshuo Yan; Juncheng Liu; Jingchun Tang (Bioresource Technology, 2024)

Unveiling the effect of different dissolved organic matter (DOM) on catalytic dechlorination of nFe/Ni particles: Corrosion and passivation effect - Cholnam Ri; Munchol Kim; Hyokchol Mun; Linan Liu; Jingchun Tang (Journal of Hazardous Materials, 2024)

Evidence that co-existing cadmium and microplastics have an antagonistic effect on greenhouse gas emissions from paddy field soils - Linan Liu; Xinzuo Yang; Rob M. Ellam; Qiang Li; Di Feng; Zhaoliang Song; Jingchun Tang (Journal of Hazardous Materials, 2024)

Active CO2 emissions from thermal springs in the Karakoram fault system and adjacent regions, western Tibetan Plateau - Xian-Gang Xie; Maoliang Zhang; Wei Liu; Yi Liu; Linan Wang; Yun-Chao Lang; Sheng Xu (Applied Geochemistry, 2024)

CNT-based water-induced generator for effective self-powered devices via superior synergism between electrokinetic and galvanic effects - Linan Xu; Wenxing Wang; Xiaoguang Li; Hongjian Yu; Xinyuan Liu; Yang Zhang; Hongyang Xu; Song Lin; Xing Yi Ling; Haitao Li (Chemical Engineering Journal, 2023)

Effect of the control area layout on the impact evaluation of cage culture - Changzi Ge; Linan Wang; Yuqun Zhang; Chunfeng Qu; Xu Liu (Ocean & Coastal Management, 2023)

Interaction between microplastic biofilm formation and antibiotics: Effect of microplastic biofilm and its driving mechanisms on antibiotic resistance gene - Zhijie Zheng; Yao Huang; Linan Liu; Lan Wang; Jingchun Tang (Journal of Hazardous Materials, 2023)

Preferential role of distinct phytochemicals in biosynthesis and antibacterial activity of silver nanoparticles - Linan Liu; Chen Yu; Shakeel Ahmad; Cholnam Ri; Jingchun Tang (Journal of Environmental Management, 2023)

Synthesis of lignin sphere-based carbon-coated nZVI nanocomposites for efficient activation of persulfate to degrade 2,4-dichlorophenol - Chengfang Zhang; Di Feng; Dong Wang; Lan Wang; Linan Liu; Jingchun Tang (Journal of Environmental Chemical Engineering, 2023)

An Underwater Triboelectric Biomechanical Energy Harvester to Power the Electronic Tag of Marine Life - Bo Liu; Taili Du; Xiaoyan Xu; Jianhua Liu; Peng Zhu; Linan Guo; Yuanzheng Li; Tianrun Wang; Yongjiu Zou; Hao Wang; Peng Xu; Peiting Sun; et al. (Journal of Marine Science and Engineering, 2023)
Implantable electronic tags are crucial for the conservation of marine biodiversity. However, the power supply associated with these tags remains a significant challenge. In this study, an underwater flexible triboelectric nanogenerator (UF-TENG) was proposed to harvest the biomechanical energy from the movements of marine life, ensuring a consistent power source for the implantable devices. The UF-TENG, which is watertight by the protection of a hydrophobic poly(tetrafluoroethylene) film, consists of high stretchable carbon black-silicone as electrode and silicone as a dielectric material. This innovative design enhances the UF-TENG’s adaptability and biocompatibility with marine organisms. The UF-TENG’s performance was rigorously assessed under various conditions. Experimental data highlight a peak output of 14 V, 0.43 μA and 38 nC, with a peak power of 2.9 μW from only one unit. Notably, its performance exhibited minimal degradation even after three weeks, showing its excellent robustness. Furthermore, the UF-TENG is promising in the self-powered sensing of the environmental parameter and the marine life movement. Finally, a continuous power supply of an underwater temperature is achieved by paralleling UF-TENGs. These findings indicate the broad potential of UF-TENG technology in powering implantable electronic tags.

Impact of different zero valent iron-based particles on anaerobic microbial dechlorination of 2,4-dichlorophenol: Comparison of dechlorination performance and the underlying mechanism - Cholnam Ri; Fengxiang Li; Hyokchol Mun; Linan Liu; Jingchun Tang (Journal of Hazardous Materials, 2023)

Remote sensing assessment of the ecological benefits provided by national key ecological projects in China during 2000–2019 - Quanqin Shao; Shuchao Liu; Jia Ning; Guobo Liu; Fan Yang; Xiongyi Zhang; Linan Niu; Haibo Huang; Jiangwen Fan; Jiyuan Liu (Journal of Geographical Sciences, 2023)

Regulation of antioxidant defense in response to heat stress in Siberian sturgeon (Acipenser baerii) - Wei Wang; Linan Gao; Wenjie Liu; Zhaohui Tian; Xiaowen Wang; Hongxia Hu (Aquaculture, 2023)

New insight into the mechanisms of preferential encapsulation of metal(loid)s by wheat phytoliths under silicon nanoparticle amendment - Linan Liu; Zhaoliang Song; Jingchun Tang; Qiang Li; Binoy Sarkar; Robert Mark Ellam; Yangyang Wang; Xiangyu Zhu; Nanthi Bolan; Hailong Wang (Science of The Total Environment, 2023)

The effects of metals and mixture exposure on lung function and the potential mediating effects of oxidative stress - Hao Zeng; Bohua Dong; Nan Wang; Wenzhe Xu; Linan Guo; Jiajia Liu; Bo Fang; Lei Zhang; Qian Wang; Wenqi Yang; Manman Wang (Environmental Geochemistry and Health, 2023)

Research on Low-Frequency Vibration Monitoring Sensor Based on a Cantilever-Beam-Structured Triboelectric Nanogenerator - Xiu Xiao; Qunyi Wang; Bohan Yao; Linan Guo; Chuanqing Zhu; Cong Zhao; Ling Liu; Minyi Xu (Journal of Marine Science and Engineering, 2023)
Vibration sensing is of great significance in offshore engineering monitoring and safety detection. This paper presented a low-frequency vibration sensor (LV-TENG) based on a cantilever-beam-structured triboelectric nanogenerator, which can perform high-precision vibration sensing while conducting vibration energy collection effectively. The LV-TENG was composed of two aluminum electrode layers, a spring steel sheet covered with polytetrafluoroethylene (PTFE) and a first-order vibration mode structured frame. Under the excitation of external vibration, the spring steel sheet undergoes first-order modal vibrations between the aluminum electrodes and generates a periodically fluctuating electrical signal in the external circuit. The vibration profile of the cantilever beam was first analyzed theoretically to provide guidance for structural design. On this basis, the influence of the main structural parameters, including the structure of the Al electrode, the thickness of the steel plate, and the electronegative materials, on the output performance of LV-TENG was experimentally investigated and the structure was optimized to enhance electrical output. The results showed that the LV-TENG can accurately sense structure vibration with a frequency of 0.1 Hz to 5.0 Hz and an amplitude of 2.0 mm to 10.0 mm. The measured output voltage followed a positive linear relationship with frequency and the fitted correlation coefficient reached 0.994. The demonstration experiment indicated that the LV-TENG is expected to provide a new avenue for low-frequency vibration monitoring and can be used for structural health monitoring analysis in marine engineering.

Nitrogen-doped biochar (N-doped BC) and iron/nitrogen co-doped biochar (Fe/N co-doped BC) for removal of refractory organic pollutants - Shakeel Ahmad; Linan Liu; Shicheng Zhang; Jingchun Tang (Journal of Hazardous Materials, 2023)

Coupling and environmental implications of in situ formed biogenic Fe–Mn minerals induced by indigenous bacteria and oxygen perturbations for As(III) immobilization in groundwater - Xinxin Zhao; Zuoming Xie; Taikun Liu; Ping Li; Fuwen Pei; Linan Wang (Science of The Total Environment, 2023)

A review of antibiotics and antibiotic resistance genes (ARGs) adsorption by biochar and modified biochar in water - Linqing Du; Shakeel Ahmad; Linan Liu; Lan Wang; Jingchun Tang (Science of The Total Environment, 2023)

Silicon (Si) modification of biochars from different Si-bearing precursors improves cadmium remediation - Linan Liu; Xinzuo Yang; Shakeel Ahmad; Xiaolong Li; Cholnam Ri; Jingchun Tang; Robert Mark Ellam; Zhaoliang Song (Chemical Engineering Journal, 2023)

Recent advances in metal–organic frameworks–derived carbon-based materials in sulfate radical-based advanced oxidation processes for organic pollutant removal - Yinghao Shi; Di Feng; Shakeel Ahmad; Linan Liu; Jingchun Tang (Chemical Engineering Journal, 2023)

Individuals with T-786C and G894T genotypes of eNOS in Chinese Han population have an increased risk of developing rheumatoid arthritis - SHAOPENG LIN; DAOQIANG LIN; LINAN QIU; YUEPING WU; XIN LIU (Journal of Genetics, 2023)

The assessment of ecological restoration effects on Beijing-Tianjin Sandstorm Source Control Project area during 2000–2019 - Linan Niu; Quanqin Shao; Jia Ning; Shuchao Liu; Xiongyi Zhang; Tingjing Zhang (Ecological Engineering, 2023)

Ball-milled Fe0/FeS2 enhanced interaction of Shewanella oneidensis MR-1 with anaerobic microbial community: Impact on 2,4-dichloronitrobenzene reduction and methane yield - Cholnam Ri; Fengxiang Li; Hyokchol Mun; Linan Liu; Jingchun Tang (Chemical Engineering Journal, 2023)

Phytolith evidence for early agriculture in the East Liao River Basin, Northeast China - Jiangyong Wang; Linan Sun; Qi Fang; Jiaxin Fu; Baojian Liu; Ying Liu; Xiangmei Kong; Honghao Niu; Guizai Gao; Meng Meng; Dongmei Jie (Archaeological and Anthropological Sciences, 2021)

Phosphorus removal from wastewater by waste concrete: influence of P concentration and temperature on the product - Xiao Liu; Huiyuan Zhong; Yong Yang; Linan Yuan; Shibo Liu (Environmental Science and Pollution Research, 2020)

Characteristics of indoor and outdoor fine particles in heating period at urban, suburban, and rural sites in Harbin, China - Wenxu Fang; Weiwei Song; Liyan Liu; Guangnian Chen; Linan Ma; Yuxuan Liang; Yujie Xu; Xueying Wang; Yehao Ji; Yu Zhuang; Amadou Hima Boubacar; Yifan Li (Environmental Science and Pollution Research, 2020)

An integrated approach for landslide susceptibility mapping by considering spatial correlation and fractal distribution of clustered landslide data - Linan Liu; Shouding Li; Xiao Li; Yue Jiang; Wenhui Wei; Zhanhe Wang; Yaheng Bai (Landslides, 2019)

Crude oil removal from aqueous solution using raw and carbonized Xanthoceras sorbifolia shells - Linan Liu; Lihua Wang; Wenhong Song; Liang Yang; Liming Yin; Shaopan Xia; Hailong Wang; Peter James Strong; Zhaoliang Song (Environmental Science and Pollution Research, 2018)

Halorubrum depositum sp. nov., a Novel Halophilic Archaeon Isolated from a Salt Deposit - Shaoxing Chen; Siqi Sun; Yao Xu; Jinting Lv; Linan Chen; Liu Liu (Current Microbiology, 2018)

Ecological stoichiometry of nitrogen, phosphorous, and sulfur in China’s forests - Yuntao Wu; Hongyan Liu; Zhaoliang Song; Xiaomin Yang; Zichuan Li; Qian Hao; Linan Liu (Acta Geochimica, 2017)

Effects of topography and vegetation on distribution of rare earth elements in calcareous soils - Zhaoliang Song; Yuntao Wu; Xiaomin Yang; Zijuan Xu; Linan Liu; Xiaodong Zhang; Qian Hao; Shaobo Sun; Guilin Han; Congqiang Liu (Acta Geochimica, 2017)

Impact of climate and lithology on soil phytolith-occluded carbon accumulation in eastern China - Xiaodong Zhang; Zhaoliang Song; Zhiqi Zhao; Lukas Van Zwieten; Jianwu Li; Linan Liu; Song Xu; Hailong Wang (Journal of Soils and Sediments, 2017)

Development of genic SSR markers from an assembled Saccharina japonica genome - Jie Peng; Linan Zhang; Xiaojie Li; Cuiju Cui; Ruina Wu; Pingping Tian; Yan Li; Yanling Liu (Journal of Applied Phycology, 2016)

Development of 27 trinucleotide microsatellite markers for Saccharina japonica using next generation sequencing technology - Linan Zhang; Jie Peng; Xiaojie Li; Yanling Liu; Cuiju Cui; Hao Wu; Ruina Wu; Pingping Tian; Yan Li (Conservation Genetics Resources, 2014)

An estimating function approach to linkage heterogeneity - HE GAO; YING ZHOU; WEIJUN MA; HAIDONG LIU; LINAN ZHAO (Journal of Genetics, 2013)

Chitosan-functionalized silk fibroin 3D scaffold for keratocyte culture - Linan Guan; Pei Tian; Hongyan Ge; Xianling Tang; Hong Zhang; Lingling Du; Ping Liu (Journal of Molecular Histology, 2013)

Effect of temperature on the development of Saccharina japonica gametophytes - Linan Zhang; Cuiju Cui; Xiaojie Li; Zhuangzhi Zhang; Shiju Luo; Guangjin Liang; Yanling Liu; Guanpin Yang (Journal of Applied Phycology, 2013)

Suppression of colorectal tumor growth by regulated survivin targeting - Binghua Li; Junkai Fan; Xinran Liu; Rong Qi; Linan Bo; Jinfa Gu; Cheng Qian; Xinyuan Liu (Journal of Molecular Medicine, 2006)